Plantas submersas e flutuantes como estados alternativos: mecanismos e efeitos na cadeia trófica de um lago raso tropical. - Moi, Dieison André (2019)
The theory of alternative stable state has predicted that the asymmetric competition by light and nutrients between submerged and free-floating plants can result in alternative states, in which free-floating plants substitute submerged plants under high nutrients levels. High levels of nutrients promote the excessive growth mats of free-floating plants, resulting in decreased availability of oxygen and light on the water column, which can have greats effects on the aquatic food chain. In addition, it is speculated that different mechanisms drive the dominance of submerged and floating plants as an alternative state. Thus, (i) understand how the change between submerged and floating plant occurs in natural shallow lakes, (ii) analyse potential trophic interactions and structure in each alternative state; and, (iii) elucidate possible mechanisms that drive the shift between these two alternative states, has been one of the great challenges in ecology. In this sense, the present study used four years of data from a tropical shallow lake to fill these gapes. The study showed that, in high nutrients levels, floating plants dominated as an alternative state shaded, in which submerged plants were absent because of the low light availability. On the other hand, in low nutrient levels, submerged plants dominated as an alternative state unshaded, being floating plants limited by nutrients competition. In shaded-state, the trophic chain was simplified, with the absence of piscivorous fish and low zooplankton and phytoplankton density. In contrast, in unshaded-state, was found one trophic chain complexity drive by piscivorous fish and high zooplankton, phytoplankton, and benthic macroinvertebrates density. Finally, different mechanisms influenced each alternative state. The unshaded-state was drive by top-down mechanisms, being that piscivorous fish had a strong negative effect on phosphorus levels, while shaded-state was driven by bottom-up mechanisms, since climate change such as extreme droughts favoured elevation of phosphorous levels. These results are an important contribution to the alternative stable state theory, regarding (i) show how the change in dominance between submerged and free-floating plant as alternative state occurs in natural freshwater ecosystem, (ii) show the negative impacts of the floating plant dominance on lake diversity and (iii) suggest that climate changes lead the floating plant dominance as an alternative state.